MATHEMATICAL MODELING OF THE DEMAND - Циганчук, Роман; Мельник, Надія (Socio-economic relations in the digital society, 2019)
Consumer choice is likely to be very likely to be simulated. Consumers make purchases, choosing from different products and taking into account their price, quality and other factors. Today in microeconomic science, for the analysis of consumer behavior, people use a serial approach that does not include quantitative utility measurements. According to this approach, the consumer is able to organize various sets of benefi ts by the degree of their attractiveness for themselves according to their own preferences system. The purpose of the study is to construct a model of demand, in which the utility function is presented in the form of products of its relations to sets of goods for sets of goods. This approach eliminates the problem of finding full and partial derivatives of the utility function in its arguments and signifi cantly expands the economic analysis of the consumer demand model. The mathematical model of consumer demand with the softened requirements concerning the differentiation of the utility function is developed. To find the necessary analysis of the number of partial derivatives, the correlation between the average and its limiting values is used. In modeling demand, we use two basic approaches: the first approach uses the construction of a utility function and indifference maps; the second approach establishes a statistical connection between demand, income and prices. The utility function must meet the requirements for the continuous change of its arguments, the continuity of the function itself and the existence of the required number of its derivatives. When solving practical problems related to demand modeling, fulfillment of such requirements is not always possible. In the work, the utility function is presented in the form of the results of its relations to the arguments on the arguments themselves. This approach eliminates the problem of finding derivatives of the utility function and significantly expands the range of tasks that are solved with the help of an economic and mathematical model of consumer demand.
Keywords: utility function; average usefulness; marginal utility; demand model